THE READING BASED INSTRUCTION TO FOSTER LEARNER AUTONOMY IN AN EFL-LEARNING COMMUNITY - Inayatus Sholihah; Pratiwi Retnanindyah; Syafi’ul Anam (Jurnal Education and Development, 2019)
This study deals with the current issue of how reading based instruction fostering learner autonomy in an EFL-learning community. Here, teaching learning activity follows the steps: pre-reading activity which consist of material orientation, whilst-reading activity which consist of material exploration and reading based instruction, and post-reading activity which consist of presentation and discussion. It is qualitative study and the data of this study were taken from observation of learner’s autonomous behaviours in the classroom while teaching-learning process. The data were analysed qualitatively through several stages, such as (1) data transcription, (2) data classification, (3) data analysis to find learner’s autonomous behaviours, and (4) data interpretations. Based on data analysis, the result of this study showed that in all of the meetings, the learners’ actions to be an autonomous learner or independent learner in the classroom consists of the action in determining their own learning, objectives, and their self-direction in order to fulfil their lesson. Moreover, autonomy here was not only associated with individualization but also all the learners’ need, skills, and motivations. Then, the instruction which is follows a structures and well prepared program that is designed is the best way to promote learner autonomy. Furthermore, the learners’ responsibility to determine their own objective was mostly influenced by their self-direction that is motivation to fulfil their lesson which is being one of the learner’s autonomy criteria.